The Role of Banking in UMKM Financing - Hasyim; Bernando Aldo Yosua Tambunan; Elisabeth Silaban; Intan Harahap (Indonesian Journal of Advanced Research, 2023)
This article aims to identify and analyze the role of banks in financing small and medium enterprises in Indonesia North Sumatra Province (SUMUT). The analytical tool used is a quantitative approach. The results of this study are that the role of banking in the development of small and medium enterprises in the province of North Sumatra is very important. This is because the role of non-bank credit and financial institutions in financing small and medium enterprises is still relatively low. The contribution of banking, especially in financial support, is when small and medium enterprises enter business development. When getting a bank loan, small and medium enterprises that are categorized as potential, feasible and bankable generally do not experience difficulties.